ANALISIS PENGARUH KUALITAS PRODUK, HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Grand Panorama Resto Semarang) - Mega Saputro, Rihasto; Kamal, Mustofa (Diponegoro Journal of Management, 2015)
The research was conducted as a decline in sales at Grand Panorama Resto Semarang for several month, so we have to know what factors that influence the purchase decision. This study aims to determine the effect of quality of product, price, quality of service and location on purchase decision on Grand Panorama Resto Semarang and which ones have the most impactThe research data was collected from 100 consumers Grand Panorama Resto Semarang. Samplingin this study using accidental sampling technique. The analysis used in this study is multiple regression analysis . Before multiple regression analysis also do validity and reliability testing and classical assumption testing. And after that also do the hypothesis testing and coefficient of determination. The data have met, test the validity of realibility ,and the assumption of the classical tillable so as to produce the regression equation is as follows : Y = 0,431 X1 + 0,079 X2 + 0,274 X3 + 0,255 X4Regression analysis showed variable of quality of product, price, quality of service, and location have a positive influence to the purchase decision. The most influential variable was a quality of product 0,431  followed by quality of service 0,274, location 0,255, and price 0,079. The analysis result using t test showed that quality of product ,quality of service , and location individually have a significant influence  on purchasing decisions except price not influence on purchasing decision.  The equation model had F value of 104,152 with a significance level of  0,000. The analysis result using coeffficient of determination was discovering about 80,6% variable of purchasing decision can be summarized by the variant of variable quality of product, price, quality of service, and location, whilst 19,4% summarized by other variable which unexplained in this research.